Di‐Spiro‐Based Hole‐Transporting Materials for Highly Efficient Perovskite Solar Cells. Issue 22 (21st May 2018) - Gao, Ke; Xu, Bo; Hong, Chaoshen; Shi, Xueliang; Liu, Hongbin; Li, Xiaosong; Xie, Linghai; Jen, Alex K‐Y
Abstract: Hole‐transporting materials (HTMs) are essential for enabling highly efficient perovskite solar cells (PVSCs) to extract and transport the hole carriers. Among numerous HTMs that are studied so far, the single‐spiro‐based compounds are the most frequently used HTMs for achieving highly efficient PVSCs. In fact, all the new spiro‐based HTMs reported so far that render PVSCs over 20% are based on spiro[fluorene‐9, 9′‐xanthene] or spiro [cyclopenta [2, 1‐b:3, 4b′]dithiophene‐4, 9′‐fluorene] cores; therefore, there is a need to diversify the design of their structures for further improving their function and performance. In addition, the fundamental understanding of structure–performance relationships for the spiro‐based HTMs is still lagging, for example, how molecular configuration, spiro numbers, and heteroatoms in spiro‐rings impact the efficacy of HTMs. To address these needs, two novel H‐shaped HTMs, G1 and G2 based on the di‐spiro‐rings as the cores are designed and synthesized. The combined good film‐forming properties, better interactions with perovskite, slightly deeper highest occupied molecular orbital, higher mobility and conductivity, as well as more efficient charge transfer for G2 help devices reach a very impressive power conversion efficiency of 20.2% and good stability. This is the first report of demonstrating the feasibility of using di‐spiro‐based HTMs for highly efficient PVSCs. Abstract : For the first time, the di‐spiro‐based hole‐transporting materials (HTMs) are designed and synthesized for perovskite solar cells (PVSCs). An impressive power conversion efficiency of 20.2% is achieved for PVSCs based on one of the HTMs with a thiophene unit that enhances interfacial coupling with perovskite, highlighting the importance of rational design, and the great potential for di‐spiro applied in HTMs for PVSCs.